Association of weight loss and weight loss maintenance following diabetes diagnosis by screening and incidence of cardiovascular disease and all-cause mortality: An observational analysis of the ADDITION-Europe trial. - Strelitz, Jean; Sharp, Stephen J; Khunti, Kamlesh; Vos, Rimke C; Rutten, Guy EHM; Webb, David R; Witte, Daniel R; Sandbaek, Annelli; Wareham, Nicholas J; Griffin, Simon J (Wiley, 2021)
AIMS: Short-term weight loss may lead to remission of type 2 diabetes but the effect of maintained weight loss on cardiovascular disease (CVD) is unknown. We quantified the associations between changes in weight 5 years following a diagnosis of diabetes, and incident CVD events and mortality up to 10 years after diagnosis. MATERIALS AND METHODS: Observational analysis of the ADDITION-Europe trial of 2730 adults with screen-detected type 2 diabetes from the UK, Denmark and the Netherlands. We defined weight change based on the maintenance at 5 years of weight loss achieved during the year after diabetes diagnosis, and as 5-year overall change in weight. Incident CVD events (n = 229) and all-cause mortality (n = 225) from 5 to 10 years follow-up were ascertained from medical records. RESULTS: Gaining >2% weight during the year after diabetes diagnosis was associated with higher hazard of all-cause mortality versus maintaining weight [hazard ratio (95% confidence interval): 3.18 (1.30-7.82)]. Losing ≥5% weight 1 year after diagnosis was also associated with mortality, whether or not weight loss was maintained at 5 years: 2.47 (0.99-6.21) and 2.72 (1.17-6.30), respectively. Losing ≥10% weight over 5 years was associated with mortality among those with body mass index <30 kg/m2 [4.62 (1.87-11.42)]. Associations with CVD incidence were inconclusive. CONCLUSIONS: Both weight loss and weight gain after screen-detected diabetes diagnosis were associated with higher mortality, but not CVD events, particularly among participants without obesity. The clinical implications of weight loss following a diagnosis of diabetes probably depend on its magnitude and timing, and may differ by body mass index status. Personalization of weight loss advice and support may be warranted.
Keywords: cardiovascular disease; diabetes complications; type 2 diabetes; weight control; Adult; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Europe; Humans; Incidence; Netherlands; Risk Factors; Weight Loss